Laser Acupuncture for Postoperative Pain Management in Cats - Marques, Virgínia I. (Evid Based Complement Alternat Med, 2015)
The aim of this study was to evaluate laser acupuncture as an adjuvant for postoperative pain management in cats. Twenty cats, undergoing ovariohysterectomy, were sedated with intramuscular (IM) ketamine (5 mg kg(−1)), midazolam (0.5 mg kg(−1)), and tramadol (2 mg kg(−1)). Prior to induction of anaesthesia, the subjects were randomly distributed into two groups of 10 cats: Laser: bilateral stomach 36 and spleen 6 acupoints were stimulated with infrared laser; Control: no acupuncture was applied. Anaesthesia was induced using intravenous propofol (4 mg kg(−1)) and maintained with isoflurane. Postoperative analgesia was evaluated by a blinded assessor for 24 h following extubation using the Dynamic Interactive Visual Analogue Scale and Multidimensional Composite Pain Scale. Rescue analgesia was provided with IM tramadol (2 mg kg(−1)), and the pain scores were reassessed 30 min after the rescue intervention. If the analgesia remained insufficient, meloxicam (0.2 mg kg(−1) IM, single dose) was administered. Data were analyzed using t-tests, the Mann-Whitney test, and the Friedman test (P < 0.05). The pain scores did not differ between groups. However, postoperative supplemental analgesia was required by significantly more cats in the Control (5/10) compared with the Laser group (1/10) (P = 0.038). Laser acupuncture reduced postoperative analgesic requirements in cats undergoing ovariohysterectomy.